Presepsi Santri Dalam Penegakan Disiplin Menggunakan Hukuman Fisik dan Non Fisik Di Pondok Pesantren - Muhammad Bagus Ahlaqih; Dzulfikar Akbar Romadlon (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This research uses a qualitative method with an inductive approach that uses thematic analysis techniques. In the research that will be involved there are ten subjects, namely, five respondents from students who have experienced punishment during the disciplinary process and five active students who are minimal in violations. Data collection methods using observation, interviews, documentation. The data analysis technique uses qualitative descriptive analysis. Thus, this study can provide insight into the character and morals of students. the factors that cause students who receive punishment in the disciplinary process and the impact of students after receiving punishment in discipline. receiving punishment in the disciplinary process at the boarding school is a process that is instilled so that students are active and firm in discipline. So it is important for administrators or caregivers to model a disciplined life in boarding schools and create a safe and respectful environment for fellow non-nurturing administrators, to support the superior character of students in carrying out discipline.